THEORIZING HUMAN ADAPTATION TO CLIMATE CHANGE FROM AN INTERNATIONAL BIOETHICAL AND BIOLEGAL PERSPECTIVE - Fanni, Simona; Contipelli, Ernani (IUS ET SCIENTIA, 2018)
In 2012, Dr. Liao, Dr. Sandberg and Dr. Roache published an interesting research, aimed at suggesting a challenging solution to climate change based on genetic manipulation: smaller human beings would individually suit better environmental challenges. Although appealing, this theory quite soon reveals its weaknesses against a legal and bioethical landscape, as it would evidently clash with human rights and the principles of international bioethics and international biolaw. Drawing inspiration from the above-mentioned research, this paper assesses the interplay between climate change and bioethical and legal implications under international law. In this respect, the horizons of genome editing are considered against the background of the relevant international reference tools, as the UNESCO Universal Declaration on Human Genome and Human Rights and the Oviedo Convention, for advancing feasible solutions offered by therapeutic interventions on human somatic cells and epigenetics as means for improving human adaptation to the adverse effects of climate change.